Les pratiques d'enseignement dans le supérieur pendant les confinements et leur persistance - Ophélie Carreras; Catherine Couturier (Centre National d'Enseignement à Distance, 2023)
This study focuses on the specific teaching modalities implemented in higher education in distance learning during lockdowns. Using a questionnaire survey, we collected reported changes in practices on several dimensions: student relations, resources available and activities offered to students, course structuring and student guidance, learning assessments, and professional development practices. We also asked teachers about their intention to continue these practices in the future. It appears that there has been few changes in practices. The only dimension on which we observe an increase is the provision of resources (pdf, videos, commented slideshows...), which reflects a focus on contents. The relational dimension with students remains poorly invested. The professional development of teachers appears to be relatively underdeveloped, but some teachers express their wish to develop it in the future, especially for the research dimension. The training and support of teachers remains essential.